Poly(ethylene oxide) layers grafted to dopamine-melanin anchoring layer: stability and resistance to protein adsorption - Pop-Georgievski, Ognen; Popelka, Štĕpán; Houska, Milan; Chvostová, Dagmar; Proks, Vladimír; Rypáček, František (Biomacromolecules, 2011)
In this study, we propose substrate-independent modification for creating a protein-repellent surface based on dopamine-melanin anchoring layer used for subsequent binding of poly(ethylene oxide) (PEO) from melt. We verified that the dopamine-melanin layer can be formed on literally any substrate and could serve as the anchoring layer for subsequent grafting of PEO chains. Grafting of PEO from melt in a temperature range 70-110 °C produces densely packed PEO layers showing exceptionally low protein adsorption when exposed to the whole blood serum or plasma. The PEO layers prepared from melt at 110 °C retained the protein repellent properties for as long as 10 days after their exposure to physiological-like conditions. The PEO-dopamine-melanin modification represents a simple and universal surface modification method for the preparation of protein repellent surfaces that could serve as a nonfouling background in various applications, such as optical biosensors and tissue engineering.
Keywords: Microscopy, Electron, Transmission; vysokoúčinná kapalinová chromatografie; zvířata; vazba proteinů; Tissue Engineering; tkáňové inženýrství; skot; Adsorption; Animals; lidé; mikroskopie atomárních sil; povrchové vlastnosti; melaniny; krevní proteiny; Coated Materials, Biocompatible; Biosensing Techniques; Melanins; transmisní elektronová mikroskopie; Protein Binding; Polyethylene Glycols; hydrofobní a hydrofilní interakce; Humans; Blood Proteins; Surface Properties; Microscopy, Atomic Force; Cattle; biokompatibilní potahované materiály; Hydrophobic and Hydrophilic Interactions; Chromatography, High Pressure Liquid; polyethylenglykoly; adsorpce; biosenzitivní techniky